2008
DOI: 10.1080/17458080802353527
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of colloidal silver nanoparticles in poly(N-vinylpyrrolidone) by γ-irradiation

Abstract: Colloidal silver nanoparticles were prepared by -irradiating Ag þ in aqueous solution in the presence of 2% polyvinyl pyrrolidone (PVP) as stabilising agent and ethyl alcohol as free radical (OH . ) scavenger. The saturated conversion dose of Ag þ into Ag was determined by UV-Vis spectroscopy and the silver nanoparticles size was characterised by transmission electron microscopy. The influence of Ag þ concentration (1-50 mM) on the saturated conversion dose and average diameter of silver nanoparticles was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The obtained results indicated that the higher the Cu 2+ ions the larger the CuCl nanoparticle size is. Results of our previous study also confirmed that the higher the initial metal ions precursor concentration (Ag + ), the larger the metal nanoparticles size (Ag nano) [16]. In addition, TEM images in Figure 1 also indicated that the morphology of nano-sized CuCl was quasispherical and the particle size distribution was of the Gaussian mode (bell-shaped distribution) with fairly narrow distribution scope.…”
Section: Dependence Of Cucl Nanoparticle Size On Initial Cu 2+ Concensupporting
confidence: 58%
“…The obtained results indicated that the higher the Cu 2+ ions the larger the CuCl nanoparticle size is. Results of our previous study also confirmed that the higher the initial metal ions precursor concentration (Ag + ), the larger the metal nanoparticles size (Ag nano) [16]. In addition, TEM images in Figure 1 also indicated that the morphology of nano-sized CuCl was quasispherical and the particle size distribution was of the Gaussian mode (bell-shaped distribution) with fairly narrow distribution scope.…”
Section: Dependence Of Cucl Nanoparticle Size On Initial Cu 2+ Concensupporting
confidence: 58%
“…There is a substantial literature on metal NPs, specially on their synthesis, which can be accomplished using different methods such as chemical reduction [33], seed-mediated [34], photochemical [35], electrochemical [36], sonochemical [37], lithography [38], galvanic replacement [39], thermal evaporation [40], radiolysis [41], sol-gel [42], laser ablation [43] or CVD [44].…”
Section: Introductionmentioning
confidence: 99%
“…During irradiation Ag + ion is reduced to Ag o atom by aq e − and H • and Ag o atoms will be agglomerated to form AgNPs that are capped by chitosan or by other stabilizers. The detail reducing mechanism of formation of AgNPs by gamma Co-60 irradiation method can be referred to the papers reported by Du et al [24] and Huang et al [25]. The UV-Vis spectra of 2 mM AgNPs stabilized by 0.5%, 1% and 2% chitosan and TEM images with particle size distribution were shown in Figure 1 and Figure 2, respectively.…”
Section: Agnps/chitosan Characterizationmentioning
confidence: 91%
“…reduction of Ag + ions to Ag o (zero-valent silver) in solution have been reported [24] [25] and the most common method is chemical reduction of silver salt precursor using chemical reducing agents [19]. In comparison with other methods, gamma Co-60 ray irradiation has been considered as an effective method with several advantages as described in our previous paper [24]. Chitosan is a natural polysaccharide derived from the deacetylation of chitin with both antibacterial property and biocompatibility [26].…”
Section: Introductionmentioning
confidence: 99%